An approach for developing diagnostic Bayesian network based on operation procedures. Issue 4 (March 2015) - Liu, Zengkai; Liu, Yonghong; Cai, Baoping; Zheng, Chao
Highlights A method to develop Bayesian network based on operation procedures is proposed. The diagnostic model consists of faults, symptoms and operation procedures. The presented approach is applied to a case study of closing BOP.